The social and political consequences of wartime sexual violence: New evidence from list experiments in three conflict-affected populations - Carlo Koos; Richard Traunmüller (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Wartime sexual violence is widespread across conflict zones and thought to leave a disastrous legacy for survivors, communities, and nations. Yet, systematic studies on i) the prevalence and ii) the social and political consequences of wartime sexual violence are fraught with severe data limitations. Based on individual-level survey evidence from three conflict-affected populations in Democratic Republic of Congo, Liberia, and Sri Lanka, we make two contributions. First, we demonstrate the potential of list experiments for overcoming under-reporting bias and estimating population-based prevalence rates of sexual violence. Second, we estimate the effect of sexual violence on key outcomes of social and political development: civic participation, interethnic relations, and political trust. Across all three populations, exposure to wartime sexual violence increases civic participation. While interethnic relations remain largely unaffected, the impact on political trust varies across contexts. This cumulative evidence suggests that survivors are more resilient to wartime sexual violence than acknowledged in prior research and policy interventions.
Keywords: C93; D71; D72; D74; 330; wartime sexual violence; list experiment; democracy; post-conflict